Teacher Strategies in Implementing Religious Moderation Values in Islamic Educational Institutions - Nurbayani, Nurbayani; Amiruddin, Amiruddin (Letiges, 2024)
The policy of Islamic Education Institutions that instil the principles of religious moderation can influence students' moderate attitudes by the nature of Islamic teachings. This article aims to explain and analyze the efforts of Islamic Religious Education (PAI) teachers in implementing the values ​​of religious moderation in Islamic Education Institutions. The approach used is qualitative with the type of research used in this discussion is using literature studies. This includes systematic identification and analysis of documents related to the research problem. The data collection used by researchers uses documentation techniques from various sources, such as notes, transcripts, books, newspapers, magazines, bulletins, journals, articles, etc. Data analysis through the stages of organizing and sorting data into patterns, categories, and basic descriptive units. The results of the study indicate the efforts of teachers in implementing the values ​​of religious moderation in learning with their extracurricular activities. Among these values ​​are Tawassut, Tawazun, I'tidal, Tasamuh, Al-Musawah, Syura, Islah, Tatawwur Wa Ibtikar, Tahaddur, Wataniyah Wa Muwatanah, and Qudwatiyah. To implement the values ​​of religious moderation in Islamic religious education subjects at Islamic Education Institutions, PAI group teachers use discussion methods, case studies, problem-based learning, role-playing and project-based learning. This study focuses on teachers' efforts in implementing the values ​​of religious moderation but does not cover students' perspectives or the long-term impacts of implementing these values. Emphasizing the importance of moderate Islamic education in an increasingly diverse and complex global context, it significantly contributes to the literature on inclusive and tolerant religious education.